2015
DOI: 10.3390/ijerph120606319
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Antifungal Agents for the Treatment of Fungal Contamination in Indoor Air Environments

Abstract: Fungal contamination in indoor environments has been associated with adverse health effects for the inhabitants. Remediation of fungal contamination requires removal of the fungi present and modifying the indoor environment to become less favourable to growth.  This may include treatment of indoor environments with an antifungal agent to prevent future growth. However there are limited published data or advice on chemical agents suitable for indoor fungal remediation. The aim of this study was to assess the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 43 publications
2
34
0
5
Order By: Relevance
“…On the contrary, Gehan et al (2009) reported that Aspergillus fumigatus and Fusarium species were resistant to 1% Virkon-S solution following 30 min and even 60 min of contact in the presence of organic materials. Similarly, Rogawansamy et al (2015) reported that a 10% concentration of Virkon-S resulted in a mean inhibition zone diameter of only 19.25 mm (± 7.08) for A. fumigatus, and…”
Section: Discussionmentioning
confidence: 91%
“…On the contrary, Gehan et al (2009) reported that Aspergillus fumigatus and Fusarium species were resistant to 1% Virkon-S solution following 30 min and even 60 min of contact in the presence of organic materials. Similarly, Rogawansamy et al (2015) reported that a 10% concentration of Virkon-S resulted in a mean inhibition zone diameter of only 19.25 mm (± 7.08) for A. fumigatus, and…”
Section: Discussionmentioning
confidence: 91%
“…Out of these, four species belong to the genus Aspergillus. Earlier research work also revealed the presence of these species in indoor environment [22][23][24][25][26]. Many of the indoor fungi cause indoor microbial pollution and also known to produce mycotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Jamur yang terdapat pada rendaman kadaver tentu saja seiring dengan perjalanan waktu akan merusak kualitas dari kadaver itu sendiri, dan yang paling berbahaya dapat menyebabkan penyakit pada individu yang bekerja maupun belajar di laboratorium anatomi, khususnya bila terjadi kondisi imunosupresi. 12,13 Beberapa contoh penyakit yang cukup berbahaya yang dapat disebabkan oleh infeksi jamur adalah pneumonia, selain infeksi pada kulit atau jaringan tubuh lainnya.…”
Section: -8unclassified